2021
DOI: 10.3390/ijms22168580
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Extracellular Vesicles for Regenerative Medicine

Abstract: Extracellular vesicles (EVs) present a great potential for the development of new treatments in the biomedical field. To be used as therapeutics, many different sources have been used for EVs obtention, while only a few studies have addressed the use of platelet-derived EVs (pEVs). In fact, pEVs have been shown to intervene in different healing responses, thus some studies have evaluated their regenerative capability in wound healing or hemorrhagic shock. Even more, pEVs have proven to induce cellular differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 69 publications
1
36
0
Order By: Relevance
“…On the other hand, due to the important role of platelets in the process of thrombosis, these are particularly susceptible to activation during blood collection and handling. This can lead to abundant ex-vivo platelet vesiculation, especially if there is a delay between sample collection and processing ( Brahmer et al, 2019 ; Taus et al, 2019 ; Tripisciano et al, 2020 ; Antich-Rosselló et al, 2021 ; Puhm et al, 2021 ). This uncontrolled release of nonphysiological EVs can adversely affect downstream EV analysis; e.g., it has been shown that contaminating platelet-derived EVs can skew the isolated miRNAs populations in patient and control samples ( Palviainen et al, 2020 ).…”
Section: Contaminants Of Extracellular Vesicle Isolates From Blood Plasma and Their Relevance For Extracellular Vesicle Isolation And Chamentioning
confidence: 99%
“…On the other hand, due to the important role of platelets in the process of thrombosis, these are particularly susceptible to activation during blood collection and handling. This can lead to abundant ex-vivo platelet vesiculation, especially if there is a delay between sample collection and processing ( Brahmer et al, 2019 ; Taus et al, 2019 ; Tripisciano et al, 2020 ; Antich-Rosselló et al, 2021 ; Puhm et al, 2021 ). This uncontrolled release of nonphysiological EVs can adversely affect downstream EV analysis; e.g., it has been shown that contaminating platelet-derived EVs can skew the isolated miRNAs populations in patient and control samples ( Palviainen et al, 2020 ).…”
Section: Contaminants Of Extracellular Vesicle Isolates From Blood Plasma and Their Relevance For Extracellular Vesicle Isolation And Chamentioning
confidence: 99%
“…In this context, platelet EVs are a potential and underexplored source of sorted bioactive molecules, including different growth factors [ 23 ], that can overcome some of the aforementioned limitations. Platelet EVs offer unprecedented perspectives for personalized therapies, since they can be obtained from autologous sources from a simple blood extraction [ 8 , 22 , 24 , 25 ]. Moreover, platelet EVs can also be obtained on a large scale from otherwise discarded expired platelet units for clinical use, and have low batch-to-batch variability in terms of growth factors composition [ 18 , 26 ], which would be reflected in EVs with a more standardized biomolecule signature.…”
Section: Introductionmentioning
confidence: 99%
“…1e). According to the Minimal Information for Studies of Extracellular Vesicles (“MISEV”) guidelines 58 , TEM was qualitatively implemented by both Western Blot showing the positive expression of the proteins ALIX, CD9, Annexin A1, TSG101 (cytosolic, membrane and marker of biogenesis of EV) in PL-derived EVs 60,61 and negative expression for calnexin, therefore suggesting the absence of nonEV structures in the preparation of EVs 62 (Fig. 1f).…”
Section: Resultsmentioning
confidence: 99%